Influence of Muscle Strength Gains on Functional Capacity Improvements following Resistance Training in Older Adults: A Linear Mixed Model Approach. (3rd April 2021) - Moura, Bruno M.; Ruas, Cassio V.; Diefenthaeler, Fernando
Abstract: Aims: By using different series of linear mixed models we investigated the influence of muscle strength gains on functional capacity (FC) improvements in older adults following resistance training (RT). Methods: Eleven healthy older adults performed a 12-week non-linear periodization leg press RT program. Leg press one-repetition maximum (1-RM), quadriceps and hamstrings concentric (Qcon and Hcon ) and eccentric peak torque (PT), and FC tests (30-s, timed-up and go [TUG], stair ascent and descent) were measured before and after RT. Results: Every one-unit change in 1-RM led to 3.38 unit change in 30-s, −0.67 unit change in TUG, −0.93 unit change in stair ascent and −0.75 unit change in stair descent, and every one-unit change in Qcon and Hcon PT led to −0.46 and −0.84 unit changes in stair ascent (p < 0.005). Conclusions: Our detailed analyses provide evidence that strength-specific gains positively influence movement-specific FC improvements in older adults following RT.